Terphenyllin Suppresses Orthotopic Pancreatic Tumor Growth and Prevents Metastasis in Mice - Zhang, Jia; Wang, Weiyi; Zhou, Yuan; Yang, Jing; Xu, Jingli; Xu, Zhiyuan; Xu, Beihua; Yan, Li; Cheng, Xiang-Dong; Li, Minghua; Qin, Jiang-Jiang (Frontiers in Pharmacology, 2020)
Pancreatic cancer (PC) is an aggressive and fatal disease with high incidences of metastasis and recurrence. However, there are no effective treatment options for the majority of PC patients, especially for those with locally advanced tumors and metastatic diseases. Therefore, it is urgently needed to develop safe and effective anti-PC therapeutic agents. We have recently identified a novel marine-derived natural product terphenyllin with potent anti-PC activity. The present study was designed to investigate the efficacy and mechanisms of action of terphenyllin in several human PC cell lines and an orthotopic PC mouse model. The results showed that terphenyllin significantly inhibited the viability of all PC cell lines with minimal effects on a normal human pancreatic cell line (HPNE). We next demonstrated the effects of terphenyllin on colony formation, apoptosis, migration, and invasion in both Panc1 and HPAC cell lines in a concentration-dependent manner. Terphenyllin also suppressed the tumor growth and metastasis in the Panc1 orthotopic mouse model. We further showed the profound effects of terphenyllin on the expression of apoptosis-associated proteins, including Bax, Bad, Puma, BimL, Bcl-2, phos-Bcl-2 (Ser70), Bcl-xL, caspase 7, and PARP, which contributed to its anti-PC activity. In summary, terphenyllin suppressed the PC cell growth and metastasis in vitro and in vivo and may be developed as an anti-PC therapeutic agent in the future.